Substrate-induced strain effect on magnetic and electrical transport properties of La0·67Ca0·33MnO3 thin films with varying orientation. (June 2019) - Li, Songbin; Wang, Chuanbin; Shen, Qiang; Zhang, Lianmeng
Abstract: This paper carries out a detailed study on magnetic and electrical transport properties of La0·67 Ca0·33 MnO3 (LCMO) thin films deposited on SrTiO3 substrates with different orientations, which provide varying degrees of in-plane tensile strain. As confirmed by the structure and morphology analyses, the homogeneous LCMO thin films with columnar grains are epitaxially grown along the orientations of the substrates, and the suffered tensile strain in the film is increasing from (100) LCMO to (111) LCMO. The obtained data suggest that the magnetic and electrical transport properties of the thin films are sensitive to the substrate-induced tensile strain. The resistivity, temperature coefficient of resistivity (TCR) and magnetoresistance (MR) of the thin films were in ascending order of (1 0 0) < (1 1 0) < (1 1 1), while the ferromagnetic-paramagnetic transition temperature (TC ), magnetization and metal-insulator transition temperature (TIM ) were in descending order of (1 0 0) > (1 1 0) > (1 1 1). Highlights: Epitaxial LCMO thin films with (100), (110) and (111) orientations were grown on SrTiO3 substrates by pulsed laser deposition. The homogeneous LCMO thin films were subjected to an in-plane tensile strain. The magnetic and electrical transport properties of the LCMO thin films were closely associated with substrate-induced tensile strain.